Can Short Psychological Interventions Affect Educational Performance? Revisiting the Effect of Self-Affirmation Interventions - Serra-Garcia, Marta; Hansen, Karsten T.; Gneezy, Uri (Psychological science, 2020)
Large amounts of resources are spent annually to improve educational achievement and to close the gender gap in sciences with typically very modest effects. In 2010, a 15-min self-affirmation intervention showed a dramatic reduction in this gender gap. We reanalyzed the original data and found several critical problems. First, the self-affirmation hypothesis stated that women’s performance would improve. However, the data showed no improvement for women. There was an interaction effect between self-affirmation and gender caused by a negative effect on men’s performance. Second, the findings were based on covariate-adjusted interaction effects, which imply that self-affirmation reduced the gender gap only for the small sample of men and women who did not differ in the covariates. Third, specification-curve analyses with more than 1,500 possible specifications showed that less than one quarter yielded significant interaction effects and less than 3% showed significant improvements among women.